Hubungan Rasa Syukur dan Resiliensi dengan Kesejahteraan Psikologis Remaja Selama Pandemi Covid-19 - Hertinjung Wisnu; Dea Ardiani; Noviana Ilhami; Tri Octiawati (Ilmu Psikologi Universitas Yudharta Pasuruan, 2022)
The government's efforts to prevent the transmission of Covid-19 through various policies have an impact on many aspects of teenagers' lives, which require adjustments and make teenagers less prosperous. The purpose of this study was to examine the relationship between gratitude and resilience with adolescent psychological well-being during the Covid-19 pandemic. This research uses correlational quantitative method. The research subjects were high school students in Surakarta with a total of 138 students. Data were collected using the Psychological Well-Being Scale, Gratitude, and Resilience. The content validity for all 3 scales moves from 0.75 to 1.00. The reliability of the psychological well-being scale is 0.797, gratitude is 0.835, and resilience is 0.876. The results of the multiple regression analysis showed that R = 0.752 with p = 0.000 (p <0.05), which means that there is a very significant relationship between gratitude and resilience with psychological well-being. The effective contribution of gratitude and resilience variables to psychological well-being is 56.6%, and there are still 43.4% of other factors that affect psychological well-being. This study shows that gratitude and resilience as individual internal factors need to be continuously developed so that they can act as protective factors so that adolescents can go through this pandemic with a prosperous psychological condition.